2022
DOI: 10.1186/s12882-022-02705-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predictors of mortality on haemodialysis in Brazil: a cohort of 5,081 incident patients

Abstract: Background Although Brazil has one of the largest populations on haemodialysis (HD) in the world, data regarding patients’ characteristics and the variables associated with risk of death are scanty. Methods This is a retrospective analysis of all adult patients who initiated on maintenance HD at 23 dialysis centres in Brazil between 2012 and 2017. Patients were censored after 60 months of follow-up or at the end of 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
6
0
4
Order By: Relevance
“…As demais variáveis na admissão encontradas associadas ao risco de morte no presente estudo foram idade, diabetes, o início da HD em hospital, o índice de massa corporal, o índice de saturação da transferrina, os níveis de hemoglobina, albumina e fosfatase alcalina e a presença de sobrecarga hídrica (Tabela 2). A associação entre estas variáveis e o risco de morte são bem conhecidas 8,[16][17][18][19][20][21] e não são o foco do presente estudo, pois já analisamos e discutimos mais detalhadamente tais associações num estudo prévio com esta mesma coorte 7 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As demais variáveis na admissão encontradas associadas ao risco de morte no presente estudo foram idade, diabetes, o início da HD em hospital, o índice de massa corporal, o índice de saturação da transferrina, os níveis de hemoglobina, albumina e fosfatase alcalina e a presença de sobrecarga hídrica (Tabela 2). A associação entre estas variáveis e o risco de morte são bem conhecidas 8,[16][17][18][19][20][21] e não são o foco do presente estudo, pois já analisamos e discutimos mais detalhadamente tais associações num estudo prévio com esta mesma coorte 7 .…”
Section: Discussionunclassified
“…O restante dos pacientes tem o tratamento coberto por convênios privados de saúde e geralmente dialisam nas mesmas clínicas que tratam os pacientes custeados pelo SUS 4 . A taxa de mortalidade entre os pacientes em HD é extremamente elevada [4][5][6][7] . No entanto, pouco se conhece acerca da sobrevida dos pacientes em HD no Brasil de acordo com a fonte pagadora do tratamento.…”
Section: Introductionunclassified
“…The rest of the patients have their treatments covered by private healthcare insurance, and generally undergo dialysis in the same clinics that treat patients funded by the SUS 4 . The mortality rate among HD patients is extremely high [4][5][6][7] . However, little is known about the survival of HD patients in Brazil according to the source paying for the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread measurement of BCM-determined fluid overload across the Nephrocare-FMC 26-country dialysis center network has facilitated large-scale observational studies, which have demonstrated strong positive associations with risk of all-cause mortality in patients requiring dialysis, independent of blood pressure (17)(18)(19). These studies used relative fluid overload derived by indexing absolute excess fluid volume to the volume of the extracellular water (ECW) compartment as the exposure, thereby allowing for comparisons between individuals (20).…”
Section: Introductionmentioning
confidence: 99%
“…These studies used relative fluid overload derived by indexing absolute excess fluid volume to the volume of the extracellular water (ECW) compartment as the exposure, thereby allowing for comparisons between individuals (20). A threshold of >15% relative fluid overload, equivalent to approximately +2.5 L absolute fluid overload (20), has often been used in analyses (17)(18)(19), while other studies have also employed the more modest threshold of >7% relative fluid overload (approximately equivalent to +1.1L absolute fluid overload) (19,21). These dialysis studies have been subject to systematic reviews (22)(23)(24)(25), but reviews of studies of heart failure and non-dialysis CKD have not been reported.…”
Section: Introductionmentioning
confidence: 99%